Mechaniation a Large Register of First Order Patient Data - Moore, Frederick J. (Methods of Information in Medicine, 1965)
In any medical record system it is necessary to link the present record of a patient to his past records in the same or other institutions. This is usually accomplished by establishing patient registers. We have studied the patient register of the Los Angeles County General Hospital (approximately 1000 000 cases) and found it feasible to mechanize this file. It is therefore realistic to contemplate development of interagency health information systems in metropolitan regions.